2014
DOI: 10.1589/jpts.26.707
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aquatic Exercise on Pulmonary Function in Patients with Spinal Cord Injury

Abstract: [Purpose] The purpose of this study was to determine the effects of aquatic exercise on pulmonary function of patients with spinal cord injury. [Subjects] The subjects were randomly allocated to an aqua group (n=10) and a land group (n=10). [Methods] Both groups trained for 60 minutes, 3 times a week for 8 weeks. Pulmonary function was assessed by measuring the forced vital capacity (FVC), forced expiratory flow rate (FER), force expiratory volume at one second (FEV1) and force expiratory volume at one second/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
0
18
0
2
Order By: Relevance
“…Aquatic exercise has the benefit of providing buoyancy for supporting body weight and reducing stress on the musculo-skeletal system and fear of falling that create barriers to exercise in some older adults [21][22][23]. Most studies examining the effects of aquatic exercise have therefore focused on adults with problems such as osteoporosis, ankylosing spondylitis, spinal cord injury, or fibromyalgia syndrome [24][25][26][27][28]. However, the few studies that have measured sleep outcomes from aquatic exercise suggest that it may produce greater benefits for sleep than land-based exercise [29][30][31][32][33] and therefore has potential benefits for older adults facing sleep difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic exercise has the benefit of providing buoyancy for supporting body weight and reducing stress on the musculo-skeletal system and fear of falling that create barriers to exercise in some older adults [21][22][23]. Most studies examining the effects of aquatic exercise have therefore focused on adults with problems such as osteoporosis, ankylosing spondylitis, spinal cord injury, or fibromyalgia syndrome [24][25][26][27][28]. However, the few studies that have measured sleep outcomes from aquatic exercise suggest that it may produce greater benefits for sleep than land-based exercise [29][30][31][32][33] and therefore has potential benefits for older adults facing sleep difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Only 4 studies provided the grade of ASIA impairment scale. [9,1921] There was a big range in terms of postinjury time from 7 months to 28 years. In terms of study design, 3 were controlled clinical trials, [9,18,22] 2 single group test–retest designs, [20,21] 1 randomized controlled trial, [19] 1 single-subject design, [23] and 1 case study.…”
Section: Resultsmentioning
confidence: 99%
“…One study used a swimming program [23] and 2 studies incorporated swimming with physiotherapeutic activities as the intervention. [18,22] One study used aquatic exercises, [19] 1 study employed aquatic exercises together with land-based exercises, [24] and 1 study combined aquatic exercises, physiotherapeutic activities, and oral baclofen as the treatment. [9] Two studies utilized underwater treadmill training as their intervention program.…”
Section: Resultsmentioning
confidence: 99%
“…Wiażewicz (2014Wiażewicz ( , 2014b reports that about 96% of aqua aerobics participants noticed health improvement. Jung, Chung, Kim, Lee, Lee (2014) reported that exercise in an aquatic environment is more effective than training applied on the ground. Kim and O'sullivan (2013) found that aquatic exercises are an effective method to reduce the risk of falling in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…One of the elements that affect such a broad interest in aqua aerobics are specific characteristics of the aquatic environment (Mosakowska, 2007). From the standpoint of physics and physiology, aqueous media are preferred in the treatment of various diseases of the musculoskeletal or neurological system, also in the pathology of heart and lungs (Jung, Chung, Kim, Lee, Lee, 2014). Katz (2003) points out that many pregnant women attend various activities taking place in an aqueous environment, because it has a significant beneficial effect on the cardiovascular system due to hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%